Ritual Perang Topat sebagai Praktik Ekologis: Kepercayaan Masyarakat dalam Pelestarian Alam - Hanapi Hanapi; Zulkarnain Zulkarnain; Ahyar Rasyidi; Lalu M. Istiqlal (Jurnal Humanitas: Katalisator Perubahan dan Inovator Pendidikan, 2026)
This study aims to analyze the Perang Topat ritual as a form of local ecological practice and as an expression of the community’s belief system in environmental conservation. The research employs a qualitative approach using an ethnoecology-based case study design. Data were collected through observation, semi-structured interviews with customary leaders, religious figures, and local community members, as well as document analysis. Data analysis was conducted using an interpretative thematic approach through coding, categorization, and inductive identification of ecological values. The findings indicate that the Perang Topat ritual functions as both a religious and social practice while embodying ecological values, including respect for nature, sustainable resource management, and the strengthening of collective awareness regarding environmental preservation. The belief systems of the Sasak (Islam) and Balinese (Hindu) communities concerning the sacredness of nature foster ecological behaviors that are transmitted intergenerationally through ritual practices. Perang Topat can therefore be understood as a form of local ecological practice that contributes to environmental conservation grounded in local wisdom.